Das Mobilitätsskelett Ein integrativer Ansatz zur mehrdimensionalen Betrachtung von urbaner Mobilität - von Behren, Sascha (Schriftenreihe / Institut für Verkehrswesen, Karlsruher Institut für Technologie, 2023)
Seemingly detached from attractive mobility alternatives in cities the car remains highly relevant in personal mobility. In order to investigate the role of the car, a new survey concept for a multidimensional analysis of urban mobility is presented: the travel skeleton. The modular design combines the collection of everyday trips in a typical week with occasional long-distance trips in a quasi-longitudinal approach. The concept also captures associated psychographic characteristics.